1982
DOI: 10.1007/bf00272366
|View full text |Cite
|
Sign up to set email alerts
|

Composition and molecular structure of chromoplast globules of Viola tricolor

Abstract: Plastoglobules have been isolated in pure form from petals of the pansy, Viola tricolor L. Their chemical composition has been determined up to a recovery of 96% dry weight. Triacyl glycerols (57%) as well as carotenoids and their esters (23%) are the main constituents. Polar lipids, proteins, alkanes, phytyl esters, plastid quinones, and steryl esters have been detected in smaller amounts (cf. Table 1). The mean diameter of chromoplast globules is 280±70 nm (corresponding to a volume of 11.7×10(6) nm(3)), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 33 publications
3
30
0
1
Order By: Relevance
“…In carotenogenic tissue, specific structures that sequester excess carotenoids have been described (Frey-Wyssling and Kreutzer, 1958). The simplest is the globule that has a high total lipid-to-protein ratio (Hansmann and Sitte, 1982). In crystalline-type chromoplasts, lycopene crystals are sequestered into membrane structures.…”
Section: Discussionmentioning
confidence: 99%
“…In carotenogenic tissue, specific structures that sequester excess carotenoids have been described (Frey-Wyssling and Kreutzer, 1958). The simplest is the globule that has a high total lipid-to-protein ratio (Hansmann and Sitte, 1982). In crystalline-type chromoplasts, lycopene crystals are sequestered into membrane structures.…”
Section: Discussionmentioning
confidence: 99%
“…The status ofthe plastids in which pigments other than carotenoids predominate is less clear. It is, however, interesting to note that the chromoplast carotenoids of yellow Viola and of Caltha make up only 23 and 14%, respectively, ofthe globule dry weight (Sitte et al 1980;Hansmann & Sitte, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Their function is not only restricted to lipid storage, but carotenoids also act as attractants to animals in ripened fruits or as light receptors in photosynthesis. Plastoglobules appear as globular osmiophilic structures not surrounded by a boundary membrane in electron microscopy (54,57), and it was suggested that they are in direct contact with the stromal surface of the thylakoid membranes and the inner envelope of plastids (75). The neutral lipids inside the plastoglobules form a hydrophobic matrix, which is surrounded by PLs, glycolipids, and proteins, which are termed plastid-lipid associated proteins (PAPs) or plastoglobulins.…”
Section: Nonprokaryotic Lipid Bodiesmentioning
confidence: 99%